A new species of lobe-lipped bat (Chalinolobus: Vespertilionidae) from southern Papua New Guinea - Parnaby, Harry E.; King, Andrew G.; Hamilton, Steve; Eldridge, Mark D.b. (Zootaxa, 2024)
The Hoary Bat Chalinolobus nigrogriseus is the only species of the genus known from the island of New Guinea. A new species of Chalinolobus from Papua New Guinea is described based on DNA sequence and morphological criteria using material previously assigned to C. nigrogriseus. The new species most resembles the eastern Australian subspecies of the Hoary Bat C. n. nigrogriseus in general size and appearance but is easily distinguished by an enlarged, rather than rudimentary lobe at the terminal outer ear margin. The new species might also be confused on external characters with smaller individuals of Australian Gould’s Wattle Bat C. gouldii, from which it differs in having bifid first upper incisors and uniform dark dorsal fur. The inclusion of C. nigrogriseus in the bat fauna of New Guinea is now in doubt, pending a re-assessment of the identity of Chalinolobus specimens in world museum collections. Locality records of all Chalinolobus spp. from Papua New Guinea are reviewed. Most localities are below 60 m elevation in coastal savannah and woodlands. The identity of specimens of C. nigrogriseus and C. gouldii from northern Australia should be reviewed to determine whether the new species also occurs in Australia.